KOMPETENSI PROFESIONAL GURU YANG BERSERTIFIKASI DAPAT MENINGKATKAN PRESTASI BELAJAR SISWA - Endang Pristiawaty (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2015)
Essential competencies professorship is professional competence, socialcompetence, and personal competence. Professional competency, competence inthe field of substance or field of study, competence areas of learning, teachingmethods, assessment systems, the value of education and guidance. Socialcompetence, competence in the field of relationship and service, communityservice. Personal competence, competence value built through behaviors thatteachers, has a personal and attractive appearance, impressive and teachersslang and "funky." The teacher called to be willing to learn how to teach well andfun learners and called to find a way of learning right. Let's just say, a teacher isnot only a profession that is determined through testing and certificationcompetence alone, but involves the heart, meaning that from the beginning theyhad dreams of becoming a teacher, a teacher who knew him, and as a noblehumanitarian duty calls followed by awards professional as well.Seritifikasi teacher is an attempt to improve the quality of teachers isaccompanied by an increase in the welfare of teachers, which is expected toimprove the quality of learning and the quality of education in Indonesia on anongoing basis.